2009
DOI: 10.1016/j.bpj.2009.08.017
|View full text |Cite|
|
Sign up to set email alerts
|

Counteraction of Urea by Trimethylamine N-Oxide Is Due to Direct Interaction

Abstract: Trimethylamine N-oxide (TMAO) is a naturally occurring osmolyte that stabilizes proteins, induces folding, and counteracts the denaturing effects of urea, pressure, and ice. To establish the mechanism behind these effects, isotopic substitution neutron-scattering measurements were performed on aqueous solutions of TMAO and 1:1 TMAO-urea at a solute mole fraction of 0.05. The partial pair distribution functions were extracted using the empirical potential structure refinement method. The results were compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
173
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(202 citation statements)
references
References 45 publications
26
173
2
1
Order By: Relevance
“…Isotopic substitution neutron-scattering measurements of ternary-component urea-TMAO mixtures in water previously suggested that TMAO interacts directly with urea through preferential hydrogen bonding (59). However, recent studies show that the interaction affinity between the two osmolytes is too weak to be relevant even at high osmolyte concentrations (60,61).…”
Section: Resultsmentioning
confidence: 99%
“…Isotopic substitution neutron-scattering measurements of ternary-component urea-TMAO mixtures in water previously suggested that TMAO interacts directly with urea through preferential hydrogen bonding (59). However, recent studies show that the interaction affinity between the two osmolytes is too weak to be relevant even at high osmolyte concentrations (60,61).…”
Section: Resultsmentioning
confidence: 99%
“…Pertinently, it has been found that elasmobranches even during the embryo development accumulate both urea and TMAO together (Barton et al, 1999). Furthermore the mechanism of urea-methylamine counteraction has been understood in terms of thermodynamic, atomic and molecular levels (Burg and Peters, 1997;Burg et al, 1999;Kumar and Kishore, 2013;Lin and Timasheff, 1994;Meersman et al, 2009;Singh et al, 2007). In recent years, there has been no such article that addresses and discusses major developments on this front.…”
Section: Introductionmentioning
confidence: 99%
“…1, Inset) adopts a skewed tetrahedral structure with a charged oxygen capable of accepting hydrogen bonds (H bonds) and three hydrophobic (methyl) groups. This amphiphilic structural arrangement makes TMAO a rather special cosolvent, because it can form H bonds with water, self-associate in a manner similar to surfactants, and show preferential interactions with or exclusion (4)(5)(6)(7)(8)(9)(10)(11)(12) from certain protein functional groups (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Indeed, these molecular properties of TMAO have been used, either individually or in combination, to rationalize its biological activities.…”
mentioning
confidence: 99%